Greenwashing and tax avoidance: Does intellectual capital moderate the relationship? - Sailendra Sailendra; Shanti Lyshandra (WIM Solusi Prima, 2026)
This study aims to analyze the effect of greenwashing on tax avoidance and examine the moderating role of intellectual capital across 68 non-financial companies listed on the Indonesia Stock Exchange that participated in the PROPER program during the 2020–2025 period. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), this research examines 408 firm-year observations. The findings indicate that greenwashing has a positive and significant effect on tax avoidance. This finding suggests that companies engaging in symbolic environmental disclosure tend to be more aggressive in implementing tax avoidance strategies as a form of opportunistic behavior. Meanwhile, intellectual capital has no significant direct effect on tax avoidance. However, the analysis demonstrates that intellectual capital serves as a moderating variable that weakens the positive effect of greenwashing on tax avoidance practices. These findings support Legitimacy Theory, illustrating how companies employ sustainability disclosures to maintain their reputation amid opportunistic tax practices. This study provides important implications for regulators and investors regarding the necessity of strengthening oversight over the consistency between sustainability disclosures, actual environmental performance, and corporate tax compliance.